2019
DOI: 10.4314/acsj.v27i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Fruit set and plant regeneration in cassava following interspecific pollination with castor bean

Abstract: The increasing demand for cassava (Manihot esculenta Crantz) for food and non-food uses in the tropics necessitates that its breeding for increased root productivity be made faster. The characteristic long breeding cycle and heterozygous nature of this crop, pose a major obstacle to its rapid genetic improvement. This study aimed at inter-pollinating cassava with castor bean (Ricinus communis), with a purpose of inducing and regenerating cassava doubled haploids (DHs). A total of 3,349 flowers from twelve elit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To determine the germinability of the pollen and ovule fertilization, about three hand-pollinated flowers were picked at two-to-three days after pollination (DAP), fixated in a solution containing glacial acetic acid and 96% ethanol (in a ratio of 1:3) and then stained with 0.1% aniline blue in 0.1% K2HPO4 before being examined for pollen tube growth as previously described in [64]. The pistils were removed from the stain, placed in a drop of glycerol on a glass slide, stigmas cut off and the ovaries dissected to extract ovules.…”
Section: In Vivo Pollen Germination and Ovule Fertilizationmentioning
confidence: 99%
“…To determine the germinability of the pollen and ovule fertilization, about three hand-pollinated flowers were picked at two-to-three days after pollination (DAP), fixated in a solution containing glacial acetic acid and 96% ethanol (in a ratio of 1:3) and then stained with 0.1% aniline blue in 0.1% K2HPO4 before being examined for pollen tube growth as previously described in [64]. The pistils were removed from the stain, placed in a drop of glycerol on a glass slide, stigmas cut off and the ovaries dissected to extract ovules.…”
Section: In Vivo Pollen Germination and Ovule Fertilizationmentioning
confidence: 99%
“…It is used in plants such as cassava ( Lentini et al, 2020 ), where hand crossing can lead to under-developed seeds to increase the chances of producing viable plants in the next generation ( Yan et al, 2015 ). Also, for hybridization between species of cassava and castor bean ( Baguma et al, 2019 ) or some Aegilops x Triticum crosses, where hybrid embryos are not naturally viable and must be nurtured to maturity in vitro ( Gill et al, 1981 ; Miller et al, 1987 )].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the embryos were advanced in their development (excised 40 DAP), which was supported by the presence of normal endosperm (Akinbo et al, 2010). Embryo rescue was used in interspecific pollination with castor bean (Ricinus communis) in early attempts to produce doubled haploids (Ramos-Abril, 2018;Baguma et al, 2019). Yan et al (2014) suggested to rescue embryos at earlier stages, from 32 to 36 DAP, when most embryos are at cotyledonary stage, the endosperm is already formed, and the embryos are visible and easier to excise from the pollinated ovules without injury.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends were reported for crosses with Manihot esculenta ssp. flabellifolia (Akinbo et al, 2010) or for wide crosses with R. communis (Ramos-Abril, 2018;Baguma et al, 2019). Therefore, the availability of an embryo rescue protocol in cassava, prior to the 2nd week after pollination, is highly relevant.…”
Section: Introductionmentioning
confidence: 99%